Legitimising disciplinary literacy : rewriting the rules of the literacy game and enhancing secondary teachers' professional habitus - McLean Davies, Larissa; Potter, Troy; Herrington, Michèle Hinton (The Australian journal of language and literacy, 2022)
This paper takes up key questions of this special issue regarding tensions and challenges in the field of literacy education by exploring how literary knowledge and skills intersect with subject area teachers' disciplinary ontologies and epistemologies. Drawing on Pierre Bourdieu's thinking tools, we analyse how literacy across the curriculum has been approached in policy and practice terms in recent decades, particularly in the context of neoliberal reforms and increasing accountability cultures. We then discuss the implications and limits of these approaches for teacher identity and professionalism, and using two initiatives in both pre-service and in-service contexts as examples, we consider ways of reconsidering the field of disciplinary literacy and the habitus of subject experts, so that secondary teachers might be best placed to support diverse learners in their classrooms. [Author abstract]